International Conference on Circuits, Communication, Control and Computing 2014
DOI: 10.1109/cimca.2014.7057779
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of two development boards for embedded system functionalities — Intel Galileo and Intel Atom board SYS9400

Abstract: The use of microcontroller boards are extremely common in day to day lives, to such an extent that it is impossible to live without them. The choice of controllers is numerous. In the market today, with rich features for every board it is hard to choose the best one. This research paper aims to compare two microcontroller boards and to point out pros and cons of both boards. The two controllers chosen are Intel Atom board SeYS9400 powered by Intel Atom processor E6xx series and Intel Galileo Board powered by q… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 3 publications
0
1
0
Order By: Relevance
“…The Galileo board was chosen for the several features that it has, like shield compatibility, Wifi/Ethernet library compatibility, familiar Arduino IDE, real time clock, micro SD card support, USB host port, serial connectivity, linux on board, works with peripheral (PCI), two-wire serial interface (TWI)/interintegrated circuit (I2C) and serial peripheral interface (SPI) support [3]. A detailed study on the performance of the Intel Galileo board can be found in [4], where a comparison between two development boards for embedded system functionalities, the Intel Galileo and the Intel Atom board SYS9400, is presented.…”
Section: Introductionmentioning
confidence: 99%
“…The Galileo board was chosen for the several features that it has, like shield compatibility, Wifi/Ethernet library compatibility, familiar Arduino IDE, real time clock, micro SD card support, USB host port, serial connectivity, linux on board, works with peripheral (PCI), two-wire serial interface (TWI)/interintegrated circuit (I2C) and serial peripheral interface (SPI) support [3]. A detailed study on the performance of the Intel Galileo board can be found in [4], where a comparison between two development boards for embedded system functionalities, the Intel Galileo and the Intel Atom board SYS9400, is presented.…”
Section: Introductionmentioning
confidence: 99%